Building Blazor WebAssembly Applications with gRPC: Learn how to implement source generators and gRPC in your Blazor apps for better performance - Pekárek, Václav (Packt Publishing, 2022)
Explore the power of Blazor WebAssembly, gRPC, and source generators for easy and quick web development Key Features Get to grips with integration between Blazor, gRPC, and source generators in real-life projectsDevelop a complete Blazor WebAssembly project that takes advantage of gRPC’s capabilitiesExplore best practices for building a high-performance web application with Blazor and C# Book Description Building Blazor WebAssembly Applications with gRPC will take you to the next level in your web development career. After working through all the essentials of gRPC, Blazor, and source generators, you will be far from a beginner C# developer and would qualify as a developer with intermediate knowledge of the Blazor ecosystem. After a quick primer on the basics of Blazor technology, REST, gRPC, and source generators, you’ll dive straight into building Blazor WASM applications. You’ll learn about everything from two-way bindings and Razor syntax to project setup. The practical emphasis continues throughout the book as you steam through creating data repositories, working with REST, and building and registering gRPC services. The chapters also cover how to manage source generators, C# and debugging best practices, and more. There is no shorter path than this book to solidify your gRPC-enabled web development knowledge. By the end of this book, your knowledge of building Blazor applications with one of the most modern and powerful frameworks around will equip you with a highly sought-after skill set that you can leverage in the best way possible. What you will learn Master routing and test your learning with demo applicationsCreate service and controller classes for your API endpointsUse gRPC with Blazor instead of REST and revamp your applicationsStudy partial classes, attributes, and more in source generatorsWrite reusable Razor components and debug your code effectivelyUnderstand the semantic model of C# codeDiscover how to read and navigate through syntax treesBuild dynamic websites without using JavaScript Who this book is for This book is for beginner C# developers who want to learn how to create more performant web apps with less code using Blazor, the gRPC protocol, and source generators. The book assumes a basic understanding of C#, HTML, and web development concepts.